Analysis of the enhancer element that controls expression of sevenless in the developing Drosophila eye. - Bowtell, D D (1991)
The sevenless gene encodes a protein-tyrosine kinase receptor expressed in a complex pattern during the development of the Drosophila melanogaster eye. We have previously shown that this pattern is regulated transcriptionally by an enhancer located in the body of the sevenless gene. Here we extend our analysis of the sevenless enhancer, defining a 475-base-pair fragment that contains elements necessary for the correct qualitative and quantitative expression of the sevenless gene. Within this fragment are sequence elements conserved in the sevenless gene of a distantly related Drosophila species and protected from DNase I digestion by nuclear extracts isolated from adult heads and imaginal discs. Partial deletions of the 475-base-pair fragment result in preferential loss of expression in different subsets of cells. These results suggest that the normal pattern of expression is generated by the combined action of separate cell-specific regulatory elements.